Antimicrobial Resistance as a Global Health Threat: The Need to Learn Lessons from the COVID‐19 Pandemic. Issue 2 (16th March 2022) - Cameron, Anishka; Esiovwa, Regina; Connolly, John; Hursthouse, Andrew; Henriquez, Fiona
Abstract: The global COVID‐19 pandemic has exacerbated existing health, social, and economic challenges and threatened progress towards achieving the UN sustainable development goals. We discuss lessons learned from the COVID‐19 pandemic for global policymaking for health security governance, with a particular focus on antimicrobial resistance. We identify One Health as the primary foundation of public health risk management owing to the collaborative, multidisciplinary, and multisectoral efforts that underpin the One Health approach and that enhance understanding of the complex interactions at the human–animal–environment interface. We discuss the narrow human‐centric focus of the One Health approach, highlight the underrepresentation of the environmental sector in One Health networks, and encourage greater representation from the environmental sector. Furthermore, we highlight the importance of the social sciences for health security research and the need for effective communication and trust. Finally, we underscore the importance of strengthened and collaborative health, social care, and disaster management systems. The application of these lessons will facilitate holistic, multisectoral, collaborative, and ethical actions on antimicrobial resistance.